The policy-driven peak and reduction of China's carbon emissions - Qi, Ye; Stern, Nicholas; He, Jian-Kun; Lu, Jia-Qi; Liu, Tian-Le; King, David; Wu, Tong (Advances in climate change research, 2020)
Pursuant to the Paris Agreement, China committed itself to peak its carbon emissions by around 2030 and to increase the non-fossil share of primary energy to 20% at the same time. The government has supported the international agreement by setting and strengthening the domestic policy targets for an earlier peak and faster reduction, aiming to contain the average global temperature increase to well below 2 °C. We develop a Kaya Inequality method to assess the time of peak and pace of reduction of China's energy-related CO2 emissions based on the national energy policy targets for 2030. We find that, despite the minor fluctuations, the current plateau essentially represents the peak emissions and should enter a phase of steady decline by around 2025, given current trends in energy consumption and decarbonization. Such developments would be consistent with the strengthened national policy target to achieve 50% of renewable power generation by 2030. However, the basic policy targets – a 20% share of non-fossil energy and 6 Gtce in total energy consumption by 2030 – would be insufficient to peak carbon emissions by around 2030. The synergy and interplay between domestic policy target setting and international climate commitments shed light on the need to elevate national climate ambitions under the Paris Agreement and beyond.